Cognitive performance in aged rats is associated with differences in distinctive neuronal populations in the ventral tegmental area and altered synaptic plasticity in the hippocampus - Sagheddu, Claudia; Stojanovic, Tamara; Kouhnavardi, Shima; Savchenko, Artem; Hussein, Ahmed M.; Pistis, Marco; Monje, Francisco J.; Plasenzotti, Roberto; Aufy, Mohammed; Studenik, Christian R.; Lubec, Jana; Lubec, Gert (Frontiers in Aging Neuroscience, 2024)
Introduction Deterioration of cognitive functions is commonly associated with aging, although there is wide variation in the onset and manifestation. Albeit heterogeneity in age-related cognitive decline has been studied at the cellular and molecular level, there is poor evidence for electrophysiological correlates. The aim of the current study was to address the electrophysiological basis of heterogeneity of cognitive functions in cognitively Inferior and Superior old (19-20 months) rats in the ventral tegmental area (VTA) and the hippocampus, having Young (12 weeks) rats as a control. The midbrain VTA operates as a hub amidst affective and cognitive facets, processing sensory inputs related to motivated behaviours and hippocampal memory. Increasing evidence shows direct dopaminergic and non-dopaminergic input from the VTA to the hippocampus. Methods Aged Superior and Inferior male rats were selected from a cohort of 88 animals based on their performance in a spatial learning and memory task. Using in vivo single-cell recording in the VTA, we examined the electrical activity of different neuronal populations (putative dopaminergic, glutamatergic and GABAergic neurons). In the same animals, basal synaptic transmission and synaptic plasticity were examined in hippocampal slices. Results Electrophysiological recordings from the VTA and hippocampus showed alterations associated with aging per se, together with differences specifically linked to the cognitive status of aged animals. In particular, the bursting activity of dopamine neurons was lower, while the firing frequency of glutamatergic neurons was higher in VTA of Inferior old rats. The response to high-frequency stimulation in hippocampal slices also discriminated between Superior and Inferior aged animals. Discussion This study provides new insight into electrophysiological information underlying compromised cerebral ageing. Further understanding of brain senescence, possibly related to neurocognitive decline, will help develop new strategies towards the preservation of a high quality of life.